Growth of pecan rootstocks with the use of liquid humus in an organic production system - Ferreira da Silva, Guilherme; Geremias Hellwig, Cristiano; Farias Barreto, Caroline; Martins, Carlos Roberto; Mello-Farias, Paulo (Comunicata Scientiae, 2023)
Pecan farming is a long-term investment which needs quality seedlings to establish an orchard. Pecan rootstocks must have a vigorous radicular system to form quality seedlings. Liquid humus, which acts as an agent that promotes their growth and development, is a bioinput that is specially used in organic production systems. This study aimed at evaluating effects of different frequencies of liquid humus application on pecan rootstock growth and development in an organic system. Liquid humus at 30% was applied every 7, 14, 21 and 28 days. The control treatment consisted of water application. The experiment was carried out with ‘Barton’ rootstocks in a greenhouse at the Embrapa Clima Temperado located in Pelotas, RS, Brazil. The following variables were evaluated 280 and 480 days after transplantation: plant height; stem diameter; leaf area; fresh and dry masses of the aerial part; main and secondary root lengths; fresh and dry masses of roots; fresh and dry masses of the main root; fresh and dry masses of secondary roots; and the Dickson Quality Index. Liquid humus increased secondary root length of pecan rootstocks, mainly when it was applied every seven days. Thus, the bioinput may be used for this purpose.